Spatial Differentiation Of The Structure Of Economics Of The Regions Of The Arctic Zone Of The Russian Federation - Baklanov, Peter Yakovlevich; Moshkov, Anatoly Vladimirovich (Economy of Regions, 2015)
The Regions located in the Arctic zone of the Russian Federation implement an important function in the development of an export potential of the country. The richest nature-resource potential of the land and the sea should be considered as the favorable factors of manufacture development in the Arctic zone. The negative factors constraining the development of the Arctic zone are as follows: severe nature-climatic conditions; considerable remoteness of the region from the subjects of the Russian Federation being socially and economically more developed; weak economic (including infrastructural) mastering of this territory; a low demographic potential of the population. The goal of the studies is to reveal the existing spatial differentiation of the economic activities in the northern latitude areas of the country. The authors have compiled several diagrams and maps to estimate the differences in the branch structure of gross value added of the subjects of the Arctic zone of Russia. Besides that, a variance of the areas' shares in comparison with the average value of the Russian Federation as a whole has been estimated. The analysis of the features of spatial differentiation of the economic activities of the Arctic regions allows us to determine the certain tendencies of the development of economic structures for the future. The article is intended for those experts and students who are interested in the problems of the development of the northern regions of the Russian Federation.